Brain-dead donor heart conservation with a preservation solution supplemented by a conditioned medium from mesenchymal stem cells improves graft contractility after transplantation - Korkmaz-İçöz, Sevil; Li, Kunsheng; Loganathan, Sivakkanan; Ding, Qingwei; Ruppert, Mihály; Radovits, Tamás; Brlecic, Paige; Sayour, Alex A; Karck, Matthias; Szabó, Gábor (American journal of transplantation, 2020)
Hearts are usually procured from brain-dead (BD) donors. However, brain death may induce hemodynamic instability, which may contribute to posttransplant graft dysfunction. We hypothesized that BD-donor heart preservation with a conditioned medium (CM) from mesenchymal stem cells (MSCs) would improve graft function after transplantation. Additionally, we explored the PI3K pathway's potential role. Rat MSCs-derived CM was used for conservation purposes. Donor rats were either exposed to sham operation or brain death by inflation of a subdural balloon-catheter for 5.5 hours. Then, the hearts were explanted, stored in cardioplegic solution-supplemented with either a medium vehicle (BD and sham), CM (BD + CM), or LY294002, an inhibitor of PI3K (BD + CM + LY), and finally transplanted. Systolic performance and relaxation parameters were significantly reduced in BD-donors compared to sham. After transplantation, systolic and diastolic functions were significantly decreased, terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL)-positive cells and endonuclease G positive cells were increased in the BD-group compared to sham. Preservation of BD-donor hearts with CM resulted in a recovery of systolic graft function (dP/dtmax: BD + CM: 3148 ± 178 vs BD: 2192 ± 94 mm Hg/s at 110 µL, P < .05) and reduced apoptosis. LY294002 partially lowered graft protection afforded by CM in the BD group. Our data suggest that PI3K/Akt pathway is not the primary mechanism of action of CM in improving posttransplant cardiac contractility and preventing caspase-independent apoptosis.
First published: 11 March 2020
Gesehen am 10.01.2022